Hubungan Pola Asuh dan Sanitasi Lingkungan dengan Kejadian Stunting Pada Balita di Kelurahan Sawahan - Khoeriyah, Salis Miftahul (Jurnal Kesehatan Samodra Ilmu (JKSI), 2024)
Background: Stunting is a problem of prolonged nutritional deficiencies due to insufficient consumption of nutrients over a long period of time, causing growth disorders in children, where children have a lower or shorter height (stunted) than the standard appropriate for their age. Objective: to determine the relationship between parenting patterns and environmental sanitation with the incidence of stunting in the Ponjong 1 health center working area. Research Methods: The study used a cross-sectional design. This study used a total sampling technique with a sample size of 45 mothers who had toddlers with stunting incidents Result: There is a relationship between parenting with the incidence of stunting in toddlers in Sawahan Gunung Kidul Village with a value of P = 0.03 (<0.05) and there is a relationship between environmental sanitation and the incidence of stunting in toddlers in Sawahan Gunung Kidul Village with a value of P = 0.007 ( <0.05) Conclusions: There is a relationship between parenting pattern and Enviromental Sanitation with the incidence of stunting in toddlers in Sawahan Gunung Kidul Village